In-vitro and in-vivo anthelmintic potential of different medicinal plants against Ascaridia galli infection in poultry birds. Issue 1 (March 2016) - RAZA, A.; MUHAMMAD, F.; BASHIR, S.; ASLAM, B.; ANWAR, M.I.; NASEER, M.U.
Abstract : Infectious diseases are major constraint that hinders the poultry industry. Among them parasitic diseases are very common and Ascaridia galli is one of the most common parasitic roundworms found in poultry. Haemorrhages, diarrhoea and listlessness are signs of infection. Parasitic infections such as A. galli are treated with chemical anthelmintics (piperazine, albendazole, levamisole, Ivermectin, benzimidazoles and fenbendazole). These synthetic chemicals can promote resistance, so there is need for alternative ways to treat the disease. Medicinal plants have the potential to combat such parasitism and the development of anthelmintic resistance appears to be very slow against such treatment. This review covers the studies related to the screening of plant materials having in vitro and in vivo anthelmintic activities against A. galli throughout the world. Medicinal plants showing in vitro anthelmintic activity include Anacardium occidentale, Allium sativum, Tribulus terrestris, Bassia latifolia, Piper betle, Morinda citrifolia L.I, Cassia occidentalis L. and Aloe secundiflora while in vivo studies include the use of Psorelia corylifolia, Piper betle, Pilostigma thonningi, Caesalpinia crista, Ocimum gratissimum and Anacardium occidentale . In conclusion, medicinal plants appear to have good anthelmintic activities in poultry and may substitute conventionally used synthetic drugs, and their use may moderate drug resistance in endemic pathogen populations and drug residues in poultry meat.